Donor-impurity-related second and third harmonic generation and optical absorption in GaAs-(Ga,Al)As 3D coupled quantum dot-rings under applied electric field (2015)
The features of some donor-impurity-related nonlinear optical properties in coupled dot-ring nanostructures are investigated with the use of the effective mass and parabolic band approximations. The electron confinement is modeled via a recently reported analytical potential, and the influence of an externally applied static electric field is taken into account. The results show that the increase in the applied field strength causes the blueshift of all the optical responses considered, whereas they can be redshifted or blueshifted depending of the impurity position. For the parameters and interlevel transitions considered in this work, the third harmonic generation is absent when the impurity moves along the same direction of the polarization of the incident resonant radiation.